Cortisol Secretion in Obesity Revisited: Lower Basal Serum and Salivary Cortisol with Diminished Cortisol Response to the Low Dose ACTH Challenge - Yael Sofer; Esther Osher; Wiessam Abu Ahmad; Yona Greenman; Yaffa Moshe; Sigal Shaklai; Marianna Yaron; Merav Serebro; Karen Tordjman; Naftali Stern (Obesity Facts)
Introduction: Some clinical resemblance may exist between obesity, particularly abdominal obesity, and Cushing’s syndrome. This has stimulated ongoing interest in the role of cortisol’s secretion pattern, control, and metabolism in obesity. Goals: The aim of the study was to investigate whether basal and stimulated levels of cortisol differ between healthy people with obesity and individuals with normal weight. Methods: Total, free, and salivary cortisol was tested at baseline state and after 1 μg ACTH stimulation in 60 healthy subjects with obesity and 54 healthy lean controls. Results: Baseline total cortisol was lower in subjects with obesity compared to lean controls (347 [265–452] nmol/L vs. 422 [328–493] nmol/L, respectively; p < 0.05). Similarly, basal salivary cortisol was significantly lower in subjects with obesity (7.5 [5.2–9.7] nmol/L vs. 10.7 [7.5–17.6] nmol/L; p < 0.05). Upon challenge with ACTH, total peak serum and salivary peak cortisol responses were significantly lower in people with obesity than in lean subjects (665.16 ± 151.8 vs. 728.64 ± 124.2 nmol/L; p < 0.05 and 31.66 [19–38.64] vs. 40.05 [31.46–46.64] nmol/L; p < 0.05, respectively). Additionally, baseline total cortisol and salivary cortisol were inversely related to BMI (r = −0.24, r = −0.27; p < 0.05 for both) and waist circumference (r = −0.27, r = −0.34; p < 0.05 for both). Conclusion: Baseline as well as peak stimulated total serum and salivary cortisol were significantly lower in subjects with obesity. It thus appears that obesity is not associated with enhanced basal or ACTH-stimulated cortisol.